Keterkaitan Pemberian Discount Pada Produk Kosmetik Dengan Konsep Predatory Pricing Dalam Perspektif Hukum Persaingan Usaha (International Forum of Researchers and Lecturers, 2023)
Giving discounts on each product is also the main target to increase the number of buyers. Discount is a price discount given by the seller to the buyer as a reward for certain activities from the buyer that are pleasant for the seller. Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktik Monopoli dan Usaha Tidak Sehat has regulated how a business actor may not practice business competition by setting prices below other business competitors. One of them is known as Predatory Pricing, which is an act of a business actor providing a very low price for his product so that his competitors are unable to compete with him and are then forced to leave the market. One example of predatory pricing is the case of giving a large discount to a cosmetic brand which indicates a lower price than other competing brands.